2019
DOI: 10.1029/2018tc005214
|View full text |Cite
|
Sign up to set email alerts
|

Initial Deformation of the Northern Tibetan Plateau: Insights From Deposition of the Lulehe Formation in the Qaidam Basin

Abstract: The Paleogene Lulehe Formation marks the onset of deposition in the Qaidam basin and preserves evidence of the initial topographic growth of northern Tibet. However, limited outcrops impede understanding of the sedimentary features of the Lulehe Formation as well as the tectonic relationship between the basin and surrounding topography. To fill this gap, we investigated core samples along the basin margin and conducted flexural modeling to estimate the topographic load of the Qilian Shan and Eastern Kunlun Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 122 publications
(364 reference statements)
1
37
0
1
Order By: Relevance
“…Compared with the widespread middle Miocene deformation across the entire Qilian Shan, the early Cenozoic deformation is just reported south of the Qaidam Basin (e.g., Clark et al, ; Jolivet et al, , ; D. Liu, Li, et al, ; Mock et al, ; F. Wang, Shi, et al, ; Y. Wang et al, ; Yin et al, ), the northern Qaidam Basin (e.g., F. Cheng et al, ; He et al, ; Jolivet et al, ; Lu et al, ; Yin et al, ; Zhuang et al, ), and parts of the Qilian Shan, such as the Xining‐Lanzhou Basin (Dupont‐Nivet et al, ; Dai et al, ; J. Zhang et al, ; Wang, Zhang, Liu, et al, ), western Qinling (Clark et al, ; Duvall et al, ), and the central‐northern Qilian Shan (e.g., Qi et al, ; He et al, ; Figure b). The Paleocene‐Eocene and widespread middle Miocene deformation suggest that the crustal shortening has extended into the northern Tibetan Plateau to reactive preexisting weaknesses shortly after the India‐Eurasia collision, followed by a phase of extensive crustal shortening across the Qilian Shan since the middle Miocene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the widespread middle Miocene deformation across the entire Qilian Shan, the early Cenozoic deformation is just reported south of the Qaidam Basin (e.g., Clark et al, ; Jolivet et al, , ; D. Liu, Li, et al, ; Mock et al, ; F. Wang, Shi, et al, ; Y. Wang et al, ; Yin et al, ), the northern Qaidam Basin (e.g., F. Cheng et al, ; He et al, ; Jolivet et al, ; Lu et al, ; Yin et al, ; Zhuang et al, ), and parts of the Qilian Shan, such as the Xining‐Lanzhou Basin (Dupont‐Nivet et al, ; Dai et al, ; J. Zhang et al, ; Wang, Zhang, Liu, et al, ), western Qinling (Clark et al, ; Duvall et al, ), and the central‐northern Qilian Shan (e.g., Qi et al, ; He et al, ; Figure b). The Paleocene‐Eocene and widespread middle Miocene deformation suggest that the crustal shortening has extended into the northern Tibetan Plateau to reactive preexisting weaknesses shortly after the India‐Eurasia collision, followed by a phase of extensive crustal shortening across the Qilian Shan since the middle Miocene.…”
Section: Discussionmentioning
confidence: 99%
“…It is also supported by provenance analyses for the Qaidam Basin, which indicate that early Cenozoic sediments in the northern Qaidam Basin were shed from the Kunlun Shan rather than the southern Qilian Shan, and provenance change occurred during early‐middle Miocene (Bush et al, ; W. Wang, Zheng, Zhang, et al, ). While Lu et al () suggest that Bush et al () may misidentify the underlying Cretaceous Quanyagou formation as the lower part of the Lulehe formation such that produce improper conclusions, they concluded that the Lulehe formation is characterized by proximal alluvial fan deposits that originated from the northern Qaidam Basin and the southern Qilian Shan based on evidence of sedimentology, facies analysis, and seismic reflection profiles (e.g., F. Cheng et al, ; Lu et al, ; Yin et al, ). Cheng et al () suggest that if both the traditional (~50 Ma) and younger (~25.5 Ma) age models are correct, the Qaidam Basin may experience diachronous basin‐fill process and the lithostratigraphic units throughout the basin are time transgressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 30 km depth (Figure 4), the low‐V zones beneath EKQB‐WQFZ seem to be limited by the Kunlun fault to the south. The Qilian block is kinematically linked with the Altyn Tagh Shan in the west for simultaneous deformation since the Paleogene (Cheng et al, 2019). Considering the seismic velocity results near the Kunlun fault (Sun et al, 2019) and the seismic anisotropy near the north Qinling fault (Hu et al, 2020), we deem that the EKQB‐WQFZ may act as a conjugate tectonic corridor to guide the middle to lower crustal flow possibly from the central Tibetan Plateau (see the thick orange arrows in Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…[20]). (c) Detailed geological map of the study area in the northern Qaidam Basin (modified from Cheng et al 2019a [21]).…”
Section: Introductionmentioning
confidence: 99%